2009
DOI: 10.1073/pnas.0810402106
|View full text |Cite
|
Sign up to set email alerts
|

Met induces mammary tumors with diverse histologies and is associated with poor outcome and human basal breast cancer

Abstract: Elevated MET receptor tyrosine kinase correlates with poor outcome in breast cancer, yet the reasons for this are poorly understood. We thus generated a transgenic mouse model targeting expression of an oncogenic Met receptor (Met mt ) to the mammary epithelium. We show that Met mt induces mammary tumors with multiple phenotypes. These reflect tumor subtypes with gene expression and immunostaining profiles sharing similarities to human basal and luminal breast cancers. Within the basal subtype, Met mt induces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
183
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(206 citation statements)
references
References 25 publications
21
183
0
1
Order By: Relevance
“…We report here a higher expression of ST8SIA1 in the basal subtype of breast tumors compared with others. Interestingly, a similar pattern was found for MET, in accordance with previous reports (38,45,46). c-Met is also associated with poor clinical outcome and considered as a possible marker for earlier recurrence and shorter survival in breast cancer patients (47)(48)(49).…”
Section: Discussionsupporting
confidence: 79%
“…We report here a higher expression of ST8SIA1 in the basal subtype of breast tumors compared with others. Interestingly, a similar pattern was found for MET, in accordance with previous reports (38,45,46). c-Met is also associated with poor clinical outcome and considered as a possible marker for earlier recurrence and shorter survival in breast cancer patients (47)(48)(49).…”
Section: Discussionsupporting
confidence: 79%
“…We also showed that both PYK2 and phospho-STAT3 positively regulate EMT in several mammary carcinoma cell lines (Figs 1c,d, 3d and 7a,b). Importantly, c-Met is also associated with EMT signature in triple-negative breast cancer 51,52 and plays a central role in breast cancer progression and metastasis 53 . Furthermore, previous studies suggest that the activation of STAT3 downstream of c-Met is crucial for cell invasion 54 , transformation and tumorigenesis 55 .…”
Section: Articlementioning
confidence: 99%
“…S3A). Next, a Cre-inducible allele of the MET receptor tyrosine kinase, which is associated with EMT and therapy resistance (18,19), and expressed at high levels in breast cancer (20)(21)(22), was introduced in KB1P-Col1a1 ESC clone A2.1 to produce K14cre;Brca1 F/F ; Trp53 F/F ;Col1a1 inv-CAG-Met-Luc (KB1P-MET) ESCs (Fig. S3B).…”
Section: Met Accelerates Mammary Tumor Development In Kb1p Chimericmentioning
confidence: 99%